What's Gaby cooking : everyday California food - Dalkin, Gaby, 1986- (Abrams, 2018)
"Gaby Dalkin shares more than 125 of her favorite simple and fresh recipes and offers a glimpse into what its like to “go coastal.” Its about always having something tasty to eat, thanks to handy and delicious pantry staples (avocado oil! quinoa! limes! dark chocolate!), as well as an arsenal of easy and healthy recipes, like Chimichurri Cauliflower Rice Bowl with Grilled Fish, Taco Skillet Bake, and Street Corn Pizza. The book covers all the staples- avocado toast, grain bowls, greens, carbs, healthy mains, cocktails, and more." --